Positive secular trend in excess body weight in adolescents: A comparative study of 2007 and 2017/2018 data. - Fernanda Ulsula de Souza; Clair Costa Miranda; Mateus Augusto Bim; Luiz Rodrigo Augustemak de Lima; Isadora Gonzaga; Gaia Salvador Claumann; Thais Silva Beltrame; André de Araújo Pinto; Andreia Pelegrini (PLoS ONE)
Background This study aimed to compare the prevalence of excess weight in adolescents living in Florianópolis, Santa Catarina, Brazil, from 2007 to 2017/2018 and assess associations with physical activity level, screen time, muscle strength, and cardiorespiratory fitness. Methods Two cross-sectional surveys were conducted with adolescents (14 to 19 years old). The body mass index was calculated from measurements of body weight (kg) and height (m2). Information on sociodemographic variables (sex, age, and economic level), screen time, and physical activity was collected using questionnaires. Motor tests were used to measure cardiorespiratory fitness and muscle strength. Results A positive secular trend in excess weight was observed in adolescents between 2017/2018 and 2007. Boys who spent more than 4h a day on screen-based activities and those with inadequate cardiorespiratory fitness were 1.96 and 3.03 times more likely, respectively, to have excess weight in 2017/2018 than in 2007. Boys (OR = 1.77) and girls (OR = 1.74) with inadequate muscle strength were more likely to have excess weight in 2017/2018 than their peers in 2007. Furthermore, boys and girls with adequate cardiorespiratory fitness had 64% and 90% lower chances, respectively, of having excess weight in 2017/2018 than in 2007. Conclusions A decade of observation revealed a positive secular trend in excess weight in adolescents, with significant associations with muscle strength, cardiorespiratory fitness, and screen time.